EFEKTIFITAS PREBIOTIK TERHADAP PERTUMBUHAN TOTAL POPULASI MIKROFLORA SALURAN PENCERNAAN IKAN MAS DAN DEPOSISI LEMAKNYA - Sanjayasari D; D.A Astuti; R. Afandi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
To preserve feed with enough energy has become important inaquaculture industry. A functional feed hold promises in replacing antibiotic toincrease feed efficiency. Prebiotic is one of functional feed which enhance the gutmicrobes. It was widely known that gut microflora hold an important position asexogenous enzyme producers to the host. This study accomplished with fourpellet treatments which contains feed with antibiotic and prebiotics. Themicroflora population were determined by MRSA (in Vivo) and the fish werereared for 6 weeks. The major parameter were gut microflora population (cfu/ml)andlipid deposition as the form of feed energy. The result showed that pellet withprebiotic has high performance on gut microflora and lipid deposition, whichconcluded has better feed efficiency.